Atom counting method for determining elemental composition of viruses and its applications in biothermodynamics and environmental science. (February 2022) - Popovic, Marko
Abstract: Quantitative physicochemical perspective on life processes has been a great asset, in bioengineering and biotechnology. The quantitative physicochemical approach can be applied to practically all organisms, including viruses, if their chemical composition and thermodynamic properties are known. In this paper, a new method is suggested for determining elemental composition of viruses, based on atom counting. The atom counting method requires knowledge of genetic sequence, protein sequences and protein copy numbers. An algorithm was suggested for a program that finds elemental composition of various viruses (DNA or RNA, enveloped or non-enveloped). Except for the nucleic acid, capsid proteins, lipid bilayer and carbohydrates, this method includes membrane proteins, as well as spike proteins. The atom counting method has been compared with the existing molecular composition and geometric methods on 5 viruses of different morphology, as well as experimentally determined composition of the poliovirus. The atom counting method was found to be more accurate in most cases. The three methods were found to be complementary, since they require different kind of input information. Moreover, since the 3 methods rest on different assumptions, results of one model can be compared to those of the other two. Graphical Abstract: ga1 Highlights: A new atom counting method is introduced for determining virus elemental composition. The new method is applicable to DNA and RNA, enveloped and non-enveloped viruses. The method is in good agreement with experimental results. A computer algorithm is proposed for implementation of the method. The model uses widely available nucleic acid and protein sequence data.